Phytochemical Screening and Fruit Quality of Commercial Eggplants - Chokthaweepanich*, Hathairat; Sriwicha, Suwalak; Auvuchanon, Anyamanee; Supapvanich, Suriyan (CURRENT APPLIED SCIENCE AND TECHNOLOGY, 2020)
Ten commercial eggplant cultivars and two allies were collected from Northeastern region of Thailand in order to examine fruit quality and screen for selected phytochemicals. Eggplants were classified into three species including Solanum torvum, S. violaceum and S. melongena. There were 10 cultivars in S. melongena (commercial eggplants) containing cv. ‘Makhuea kai tao khaw’, ‘Makhuea khuen’, ‘Makhuea pro chao phraya’, ‘Makhuea pro look lai’, ‘Makhuea pro muang’, ‘Makhuea tor lae kaew’, ‘Makhuea tor lae khaw’, ‘Makhuea yao kaew’, ‘Makhuea yao khaw’, and ‘Makhuea yao muang’. The analysis indicated that there were significant differences (p £ 0.05) in fruit quality traits including color, thickness, hardness, TSS and moisture. All samples could be divided into three groups based on fruit color including white, purple, and green groups. The commercial eggplants had more thickness than S. torvum and S. violaceum, but these two species had more TSS contents than commercial eggplants. The results of phytochemical screening showed that S. torvum tended to have higher alkaloid, tannin, saponin and steroid contents from the staining technique. Furthermore, ‘Makhuea yao muang’ showed the highest DPPH radical scavenging capacity (49.33%) compared to all others. The principal component and cluster analysis based on correlation of fruit traits and phytochemicals showed that all commercial eggplants were clustered in the same group. The correlation analysis indicated that TSS contents positively correlated with saponin and steroid, while TSS contents negatively correlated with thickness and moisture contents. As this study, commercial eggplants showed higher fruit quality and antioxidant activity than related species. Keywords: eggplant; Solanum spp.; fruit quality; phytochemicals; antioxidant activity *Corresponding author: Tel.: (+66)939159615 E-mail: hathairat.ch@ku.th